Faktor-Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Property and Real Estate Yang Terdaftar di BEI - Deasy Arisandy Aruan; Hanna Limbong; Brando Silitonga; Maulidanur Aceh; Nofanyiu Bernadett Br Samosir (Politeknik Ganesha Medan, 2021)
This study aims to determine the effect of liquidity, fixed assets, and firm size on profitability in property and real estate industry sub sectors listed in Indonesia Stock Exchange for the 2016-2019 period. The population in this study were all companies in property and real estate industry sub sector listed in Indonesia Stock Exchange for 2016-2019 period, amounting to 62 companies with a sample of 23 companies. The sampling technique used was purposive sampling. The method of analysis used in this research is the multiple linear regression method. This research uses quantitative research. This type of research used in this research is descriptive quantitative. The nature of research in this study is explanatory. The results of this study indicate that partially liquidity have no significant effect on profitability and fixed assets have no significant effect on profitability, while firm size have a negative and significant effect on profitability in the property and real estate sub-sector listed on the Indonesia Stock Exchange for the 2016-2019 period. Based on simultaneous liquidity, fixed assets, firm size have a significant effect on profitability in the property and real estate industry sub sector listed in Indonesia Stock Exchange for the 2016-2019 period.